Has the frequency of complicated appendicitis changed in children in the first year of the COVID-19 pandemic? - Tülin Öztaş; Salim Bilici; Ahmet Dursun (SpringerOpen, 2023)
Abstract Background The COVID-19 pandemic period suggests that the rate of complications may have increased in patients requiring surgical treatment due to the fact that they could not come to the hospital at the onset of the symptom. This study aims to evaluate the difference in the frequency of complicated appendicitis and postoperative complications in the COVID-19 pandemic. Patients included those who underwent appendectomy in 1 year before the COVID-19 pandemic and in the first year of the pandemic. The patients were categorized into two groups: pre-pandemic and pandemic periods. Clinical and histopathology results were compared between the pre-pandemic and pandemic periods. Results A total of 407 patients were included in the study, 207 of whom were included during the pre-pandemic and 200 of whom during the pandemic period. The mean time to hospital admission after the onset of symptoms was 1.3 ± 0.9 days, pre-pandemic, and 1.4 ± 0.8 days during the pandemic group. In the pre-pandemic group, 0.4% intrabdominal abscess developed and 37.5% complicated appendicitis was detected. In the pandemic group, it was found that there were 1% abscess, 0.5% wound infection, 0.5% brid ileus, and 31.9% complicated appendicitis. The pre-pandemic group length of hospitalization was 2.4 ± 0.8 days, and the pandemic was 2.1 ± 0.9 days There was no difference between pre-pandemic and pandemic groups in terms of age, gender, white blood cell count, duration of symptoms, postoperative complications and frequency of complicated appendicitis, and duration of hospitalization. Conclusions In the first year of the COVID-19 pandemic, we found that the rate of complicated appendicitis and postoperative complications were not different from pre-pandemic.